2018
DOI: 10.1159/000494078
|View full text |Cite
|
Sign up to set email alerts
|

Lambert-Eaton Myasthenic Syndrome Caused by Nivolumab in a Patient with Squamous Cell Lung Cancer

Abstract: Lambert-Eaton myasthenic syndrome (LEMS) is a representative paraneoplastic neurological syndrome. Recently, nivolumab, an anti-programmed cell death 1 inhibitor, has been approved for advanced non-small-cell lung cancer. Careful attention should be paid to immune-related adverse events (irAEs), including neurotoxicity. We herein report a 73-year-old woman with LEMS that occurred during nivolumab treatment for pulmonary squamous cell carcinoma. After the 20th week of nivolumab, she experienced various neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…In our literature search, we also found one case of LEMS in a patient with squamous cell lung cancer which was attributed to ICI [14]. In this case, the patient had squamous cell lung cancer which is less commonly associated with LEMS.…”
Section: Discussionmentioning
confidence: 96%
“…In our literature search, we also found one case of LEMS in a patient with squamous cell lung cancer which was attributed to ICI [14]. In this case, the patient had squamous cell lung cancer which is less commonly associated with LEMS.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have reported detection of Ma2 IgG (n = 6) among CNS irAE with variable cancer subtypes, not compatible with typical oncological association (germ cell tumors) of Ma2 IgG . As indications for cancer immunotherapies grow, cases of classic paraneoplastic phenotypes are also reported; for example, limbic encephalitis in association with anti‐Hu, antineuronal nuclear antibody type‐1, and Lambert–Eaton myasthenia syndrome in association with P/Q type voltage gated calcium channel antibodies . It is possible that the proportion of cases with classic paraneoplastic phenotypes in association with specific malignancies such as small cell cancer may become more apparent .…”
Section: Atypical Overlapping Spectrum Of Irae‐nmentioning
confidence: 98%
“…Except a case of pre‐synaptic Lambert‐Eaton myasthenic syndrome, only cases of post‐synaptic irMG have been described. Impairment of neuromuscular transmission on electrodiagnostic tests is not often reported.…”
Section: Clinical Syndromes and Presentationsmentioning
confidence: 99%
“…Therefore, a thorough evaluation should be conducted each time a pns‐irAEs is evoked, including CK and troponins dosage, as the risk of overlapping myocarditis is significant . Testing for onconeural and organ‐specific autoantibodies should be performed based on presenting clinical phenotype: anti‐AChR, anti‐MuSK, anti‐Ca ++ channel and striatational antibodies in patients with suspected irMG, systemic autoimmunity (ANA, dsDNA, anti‐SNA, and ANCA) and anti‐ganglioside antibodies in patients with peripheral neuropathies, and myositis‐associated antibodies in patients with suspected irMyositis . The suspicion of a neuromuscular disease should automatically impose distal and proximal NCS and ENMG of all four limbs.…”
Section: Management Of Peripheral Nervous System Immune‐related Advermentioning
confidence: 99%